Post-amputation reactive oxygen species production is necessary for axolotls limb regeneration - Carbonell-M, Belfran; Zapata Cardona, Juliana; Delgado, Jean Paul (Frontiers in Cell and Developmental Biology, 2022)
Introduction: Reactive oxygen species (ROS) represent molecules of great interest in the field of regenerative biology since several animal models require their production to promote and favor tissue, organ, and appendage regeneration. Recently, it has been shown that the production of ROS such as hydrogen peroxide (H2O2) is required for tail regeneration in Ambystoma mexicanum. However, to date, it is unknown whether ROS production is necessary for limb regeneration in this animal model. Methods: forelimbs of juvenile animals were amputated proximally and the dynamics of ROS production was determined using 2'7- dichlorofluorescein diacetate (DCFDA) during the regeneration process. Inhibition of ROS production was performed using the NADPH oxidase inhibitor apocynin. Subsequently, a rescue assay was performed using exogenous hydrogen peroxide (H2O2). The effect of these treatments on the size and skeletal structures of the regenerated limb was evaluated by staining with alcian blue and alizarin red, as well as the effect on blastema formation, cell proliferation, immune cell recruitment, and expression of genes related to proximal-distal identity. Results: our results show that inhibition of post-amputation limb ROS production in the A. mexicanum salamander model results in the regeneration of a miniature limb with a significant reduction in the size of skeletal elements such as the ulna, radius, and overall autopod. Additionally, other effects such as decrease in the number of carpals, defective joint morphology, and failure of integrity between the regenerated structure and the remaining tissue were identified. In addition, this treatment affected blastema formation and induced a reduction in the levels of cell proliferation in this structure, as well as a reduction in the number of CD45+ and CD11b+ immune system cells. On the other hand, blocking ROS production affected the expression of proximo-distal identity genes such as Aldha1a1, RARβ, Prod1, Meis1, Hoxa13, and other genes such as Agr2 and Yap1 in early/mid blastema. Of great interest, the failure in blastema formation, skeletal alterations, as well as the expression of the genes evaluated were rescued by the application of exogenous H2O2, suggesting that ROS/H2O2 production is necessary from the early stages for proper regeneration and patterning of the limb.